Sistem dan Prosedur Akuntansi Pembelian Persediaan Bahan Baku Sparepart di PT. Bengkalis Dockindo Perkasa - Gusti Eko Purnomo; Husni Mubarak (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
This study aims to find out about the accounting information systems and procedures for purchasing spare parts raw materials that are applied to PT. Bengkalis Dockindo Perkasa whether it is in accordance with standard operating procedures. This study uses a qualitative descriptive analysis method because the data concerning accounting and other data support this research. Based on the results of the research, the company has a minimum stock to repair ships and manufacture other products, but there are some raw materials that are not available in the warehouse due to requests from consumers, so the company must purchase raw materials in an indented manner through the selected supplier. The existence of an accounting information system that regulates the inventory purchasing process should be able to take into account when and how many companies will purchase spare parts raw material inventory. Due to uncertain orders from the field, it is difficult to estimate the company's raw material purchases.Keywords: Accounting information system, purchase of raw material inventory.